The Effectiveness of Specific Infection Control Interventions - Njood ahmad alasmari,; Basel Mohammed Saad Alyahya,; Abdul Hakem Mohamed Saad Al Sumrani,; Naief Hamad Alameel,; Abdulrahman Abdullah M Alshehri,; Zayd Abdullah Ali Aseri,; Moshari Nasser Tami Algarni,; Moshabab Abdullah M asiri,; Fahad Saeed Almanbahi,; Abdullah Muzhir Mohammed Alqahtani,; Abdullah Mtaab Nahad Alotaibi,; Nasser Mohammed alzahrani,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Infections associated with healthcare are a major cause of morbidity and mortality. A large number of intervention studies have been conducted to address these healthcare-associated infections. There are existing reviews and guidelines that summarize the evidence of the effect of many infection prevention and control interventions. This study provides a formal overview and summaries of studies evaluating some less commonly assessed interventions that have previously not been summarized in existing reviews. Many types of healthcare-associated infections are largely preventable through the implementation of evidence-based infection prevention and control measures. Such measures have been shown to be cost-effective. The effectiveness of several key infection prevention and control interventions has been established with a range of evidence from randomized and non-randomized studies. However, less commonly used interventions may not have had their effectiveness formally assessed or the evidence summarized. This paper aim at identifying, describing, and summarizing the findings of studies that have evaluated the effects of specific infection prevention and control interventions on any type of healthcare-associated infection. The interventions could either be primary components of standard precautions, additional single interventions, or additional bundled interventions.